Coronary microvascular dysfunction: a review of its association with extracardiac organ pathologies - Yuting Duan; Yuting Duan; Jia Liu; Jia Liu; Shan Wang; Shan Wang; Tongxiao Luan; Tongxiao Luan; Jing Zhou; Ziwei Cui; Ziwei Cui; Aohua Wang; et al. (Frontiers in Cardiovascular Medicine)
Coronary microvascular dysfunction (CMD) is a high-risk factor for numerous cardiovascular events, and there is an increasing focus on the diagnosis and treatment of CMD itself or its association with cardiovascular diseases. However, some evidences suggest potential associations between CMD and multiple extracardiac pathologies, such as cerebrovascular, renal, pulmonary, retinal, hepatic, immune system diseases, and cancer. A shared pathological mechanism may underlie these connections, yet the relationship between CMD and other organs and systemic diseases remains unclear. Therefore, this review comprehensively assesses the current evidence base for the interplay between CMD and a range of systemic diseases, highlighting the need for a more integrated diagnostic and therapeutic approach.